Exposure of children to ultrafine particles in primary schools in Portugal - Rufo, João Cavaleiro (2016)
Children spend a large part of their time at schools, which might be reflected as chronic exposure. Ultrafine particles (UFP) are generally associated with a more severe toxicity compared to fine and coarse particles, due to their ability to penetrate cell membranes. In addition, children tend to be more susceptible to UFP-mediated toxicity compared to adults, due to various factors including undeveloped immune and respiratory systems and inhalation rates. Thus, the purpose of this study was to determine indoor UFP number concentrations in Portuguese primary schools. Ultrafine particles were sampled between January and March 2014 in 10 public primary schools (35 classrooms) located in Porto, Portugal. Overall, the average indoor UFP number concentrations were not significantly different from outdoor concentrations (8.69 × 10(3) vs. 9.25 × 10(3) pt/cm(3), respectively; considering 6.5 h of indoor occupancy). Classrooms with distinct characteristics showed different trends of indoor UFP concentrations. The levels of carbon dioxide were negatively correlated with indoor UFP concentrations. Occupational density was significantly and positively correlated with UFP concentrations. Although the obtained results need to be interpreted with caution since there are no guidelines for UFP levels, special attention needs to be given to source control strategies in order to reduce major particle emissions and ensure good indoor air quality.